2010
DOI: 10.1177/112067211002000325
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Chamber Measurements Taken with Pentacam: An Objective Tool in Laser Iridotomy

Abstract: This study confirms previous reports of increased anterior chamber volume and angle after LPI and Pentacam is a good objective instrument to demonstrate the efficacy of LPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 12 publications
1
22
0
3
Order By: Relevance
“…Using Scheimpflug photography in a group of 37 Canadian primary angle closure suspects, LPI leads to a significant increase of ACV and ACA but left ACD unchanged [21]. The same was previously described in a group of 20 Italian patients who underwent LPI due to a high risk of developing acute angle closure [22]. Jain et al [23] found in 68 patients of Indian descent which were treated with LPI for primary angle closure that LPI leads to a significant increase of ACV and peripheral anterior chamber depth but not central Fig.…”
Section: Discussionmentioning
confidence: 57%
“…Using Scheimpflug photography in a group of 37 Canadian primary angle closure suspects, LPI leads to a significant increase of ACV and ACA but left ACD unchanged [21]. The same was previously described in a group of 20 Italian patients who underwent LPI due to a high risk of developing acute angle closure [22]. Jain et al [23] found in 68 patients of Indian descent which were treated with LPI for primary angle closure that LPI leads to a significant increase of ACV and peripheral anterior chamber depth but not central Fig.…”
Section: Discussionmentioning
confidence: 57%
“…Our findings agree with previous studies regarding the increase in ACV and ACA. 5,[20][21][22][23] In contrast, it is controversial whether LPI deepens the CACD or not. 21 reported a significant increase in CACD after pilocarpine administration.…”
Section: Discussionmentioning
confidence: 88%
“…The changes in ACA, CACD, peripheral AC depth, and central corneal thickness have been documented previously. 5,[20][21][22][23] The device used in these studies is almost always the Pentacam (Oculus; Optikgera¨te GmbH, Wetzlar, Germany), which has been shown to be accurate and reproducible in quantifying AC parameters. 27 In our study we used the Sirius device, which is basically similar albeit slightly different, and as far as we know it has not been used previously in the evaluation of AC parameters after LPI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations